Psychological issues of the relationship between self-esteem and aggression in students studying in different faculties - Jabbarov, Rashid (2023)
The article is devoted to the study of psychological issues of the relationship between self-esteem and aggression in students studying in different faculties. The main goal here is to study the effect of the levels of self-esteem on the levels of aggression and to reduce aggression by developing self-esteem. 186 students (94 technical faculty, 92 humanities faculty) who studied in the 2nd year participated in the research. According to the study, there is a relationship between the level of self-esteem of students and the level of aggression, and these relationships are significant at p=0.01 and p=0.05. It became clear that the higher the level of self-esteem, the lower the levels of aggression. In addition, it was found that there is a statistically significant relationship between students' self-esteem and aggression, academic achievement and self-actualization. A direct relationship between self-esteem and self-actualization was found (r=0.276; p=0.002). Research has shown that there is a significant relationship between academic achievement and self-esteem. This fact supports the positive relationship between self-esteem and self-attitude. The higher the student's self-esteem level, the more important academic achievement or educational value is to him (p<0.002 level). Thus, depending on the level of self-esteem, aggressive behavior is manifested. This happens at the same level for both technical and humanitarian faculties. The facts show that the aggressive behavior of students with low academic achievement is a psychological defense mechanism, which mediates false self-esteem.